WHAT IS THE RIGHT, ARCHIPELAGIC SEA LANES AND PASSAGE? (ACCORDING TO UNCLOS 1982 AND PRACTICE) - Lestari, Maria Maya (UI Scholars Hub, 2021)
The Right, Archipelagic Sea Lanes, and Passage are a new concept in international law of the sea, which only exists and applies to archipelagic states. This concept was born as a result of world recognition of the existence of an archipelagic state. Indonesia is the only archipelagic state in the world to apply this concept. Therefore, using doctrinal research will be studied of definition, historical background, and law regarding the concept of the archipelagic sea lanes, which has been approved by the United Nations Convention of the Law of the Sea 1982 (UNCLOS 1982). This paper also describes all states’ rights to cross the archipelagic sea, archipelagic sea lanes passage as a lane, passage as an activity to get through from one and another part of the high seas, or exclusive economic zone.